Perception of people living in favela about fintech - Arvis, Nicolas Jean Albert (2021)
Access to basic financial services, having a bank account, a payment card, the possibility to make transfers is a condition to have a decent standard of living. Especially in a world where cash is less and less used. Lack of access to financial services is a recurring problem among the world's poorest populations. In Brazil, part of this population is concentrated in marginal neighborhoods called "favelas" and is excluded from the Brazilian financial system. In this context of economic exclusion, fintechs bring an innovative wind to the financial and banking world by breaking down prices and digitizing finance. Based on this observation, the thesis aims to determine the perception of fintechs by resident, fintechs offering them better access to financial and banking services. The methodological approach of this thesis is to combine interviews in the favelas, with people who live and work there, and academic research on the subject. The results show that the perception of fintechs is excellent because fintechs can improve the daily lives of favela residents, especially by reducing banking fees and allowing them to create an account without income requirements. All these advances have allowed some Brazilians living in favelas to have greater financial stability, and therefore a better standard of living.